DEVELOPMENT OF MATHEMATICAL LKPD BASED ON SCIENTIFIC APPROACH TO IMPROVE STUDENTS' MATHEMATICAL PROBLEM SOLVING AT SD NEGERI 1 RIMO - Yenni Yamin; E. Elvis Napitupulu; Fauziyah Harahap (Sensei International Journal of Education and Linguistic, 2022)
This study aims to describe the validity, feasibility, and effectiveness of the LKPD Mathematics based on a scientific approach to improve students' mathematical problem solving abilities. This research is research & development. While the research design used is a 4D Thiagarajan study. The research subjects were conducted to fourth grade teachers and 27 fourth grade students, as well as three validator experts. Data was collected by means of questionnaires, tests, and interviews. Based on the results of material expert validation, an average score of 87.96% was obtained, then the learning design expert validation obtained an average score of 95.31%, and linguist validation obtained an average score of 93.75%. When viewed from the number of three expert validators, an average score of 92.34% was obtained with the LKPD category being very valid and feasible to use. While the results of the student response questionnaire based on small group trials and field trials obtained an average score of 94.95% with a very good category. To find out the improvement of students' mathematical problem solving, the researchers gave pre-test and post-test questions. From the results of the pre-test and post-test, it can be seen that there is an increase in students' mathematical problem solving abilities. The students' pre-test results obtained an average of 54.28% and the post-test results obtained an average of 73.33%. Based on the n-gain score assessment criteria, the effectiveness of the Mathematics LKPD based on a scientific approach obtained a value of 0.41, a score range of 0.3 g <0.7 was classified in the medium criteria. This shows that the LKPD Mathematics based on a scientific approach is effective in improving students' mathematical problem solving abilities